Expatriatism in Khaled Hosseini's The Kite Runner and Mohsin Hamid's The Reluctant Fundamentalist - Zohreh Ramin; Ilham Ward (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
The September 11 attacks were world-changing events. Contemporary historians divide the history of the modern world into pre- and post-9/11. The metropolitan reaction was controversial. The Metropolis united against what is dubbed